2011
DOI: 10.1055/s-0031-1275170
|View full text |Cite
|
Sign up to set email alerts
|

Workhorse Flaps in Chest Wall Reconstruction: The Pectoralis Major, Latissimus Dorsi, and Rectus Abdominis Flaps

Abstract: Large and life-threatening thoracic cage defects can result from the treatment of traumatic injuries, tumors, infection, congenital anomalies, and radiation injury and require prompt reconstruction to restore respiratory function and soft tissue closure. Important factors for consideration are coverage with healthy tissue to heal a wound, the potential alteration in respiratory mechanics created by large extirpations or nonhealing thoracic wounds, and the need for immediate coverage for vital structures. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 25 publications
0
81
0
5
Order By: Relevance
“…As in previous studies, abdominal flap has been used to reconstruct various chest wall defects ; pedicled full‐thickness abdominal flap was eventually used to cover the extensive anterior chest wall defect following major electrical burn in this study, as this flap is easy to design and harvest with adequate blood supply. On the other hand, the best time to perform the operation is another important factor.…”
Section: Discussionmentioning
confidence: 96%
“…As in previous studies, abdominal flap has been used to reconstruct various chest wall defects ; pedicled full‐thickness abdominal flap was eventually used to cover the extensive anterior chest wall defect following major electrical burn in this study, as this flap is easy to design and harvest with adequate blood supply. On the other hand, the best time to perform the operation is another important factor.…”
Section: Discussionmentioning
confidence: 96%
“…For reconstruction of the chest wall defects, the most commonly used muscles are latissimus dorsi and pectoralis major;[7] sometimes, omentum is also used. [3] However, in our case, there was deep second-degree burn on the back, thus precluding use of latissimus dorsi muscle flap.…”
Section: Discussionmentioning
confidence: 99%
“…A 2002 study also showed that one-stage debridement and reconstruction is better than conventional repair techniques [18]. Among the most commonly used donor sites for chest wall reconstruction are the pectoralis major and rectus abdominis as either muscle or myocutaneous flaps [19]. Immediate debridement combined with pectoralis major flap has been shown to minimize morbidity and mortality [20].…”
Section: Discussionmentioning
confidence: 99%